MODIFYING OF CAST IRON WITH ULTRADISPERSE ADDITIVES - F. I. Rudnitsky; S. A. Kulikov (Литьë и металлургия, 2017)
The composition, structure, methods of receipt of ultradisperse materials (UDM) and the prospect of their application in engineering procedures of foundry production are considered. Positive influence of UDM when entering in fusion on structure and properties of the gray cast iron intended for production of castings of motor group is established.